2013
DOI: 10.1186/1810-522x-52-42
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of adult Drosophila antennae by high-throughput sequencing

Abstract: Background: Antennae of fruit flies are the major organs responsible for detecting environmental volatiles, e.g., egg-laying substrates. An adult antenna contains many sensilla full of olfactory sensory neurons, where olfactory receptor (Or) genes are expressed. Each sensory neuron only expresses up to three receptors, making it difficult to estimate expression levels by conventional methods. In this study, we applied Illumina RNA sequencing (RNA-seq) to study the expression levels of Or and other genes in fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…The expression of such receptors is in accordance with results from other RNAseq studies of the D. melanogaster antenna. In those studies, multiple genes previously identified by in situ hybridization or through reporter gene analyses to be only expressed in larvae or the maxillary palps were also detected in adults [42,43]. The functional significance of this, if any, remains to be determined.…”
Section: (B) Population Differences In Electrophysiological Responsesmentioning
confidence: 99%
“…The expression of such receptors is in accordance with results from other RNAseq studies of the D. melanogaster antenna. In those studies, multiple genes previously identified by in situ hybridization or through reporter gene analyses to be only expressed in larvae or the maxillary palps were also detected in adults [42,43]. The functional significance of this, if any, remains to be determined.…”
Section: (B) Population Differences In Electrophysiological Responsesmentioning
confidence: 99%
“…Interestingly, MA‐biased genes included a relatively small number of chemosensory genes, but notably contain many immune‐related genes, including antimicrobial peptides such as attacin, defencin, cecropin, and diptricin (Figure 2c; see the full list in Table S6). Interestingly, D. melanogaster also upregulated for the immune‐related genes in MA, when males were not encountered with females (Shiao et al, 2013). However, the D. melanogaster males in courting behavior decrease expression of some immune response genes, probably correlated with the decreased immunity in mated males (Carney, 2007; McKean & Nunney, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…; Shiao et al . ). These chemosensory genes include gustatory (GR), odorant (OR) and ionotropic (IR) receptors (Hallem et al .…”
Section: Introductionmentioning
confidence: 97%